Reported experiences of bereavement support in Western Australia: a pilot study. (22nd April 2014) - Aoun, Samar M.; Breen, Lauren J.; Rumbold, Bruce; Howting, Denise
Abstract Objective: This article describes the pilot testing of a community survey to ascertain the experiences and needs of people who were bereaved 6–24 months before the survey. The pilot study aimed to assess the feasibility and acceptability of the survey and test the theoretical public health model for bereavement support. Methods: A postal survey was used to collect information from clients of three funeral providers in Western Australia in 2012. Results: The findings confirmed the feasibility and acceptability of the survey questions. The analysis of the demographic characteristics, experience of bereavement and satisfaction with support revealed differential needs that align with the expectation of low, moderate and high risk, as articulated in the public health model. Conclusions: The data provided tentative empirical support for the public health model of bereavement support. This is the first empirical test of this model nationally and internationally. Implications: Considering the lack of evidence to guide development and allocation of bereavement programs in Australia, a larger survey will enable us to determine how the support needs of each of the three groups of bereaved people should be serviced. This is important for cost‐effective and equitable resource allocation.